Investigation of the interfacial fusion of welded aluminum foam sandwich panels by synchrotron radioscopy - Xixi Su; Qiang Gao; Zhanhao Feng; Xi Sun; Peng Huang; Guoyin Zu (Materials Research Letters, 2023)
The pore fusion behavior of the core layer interface in the welded aluminum foam sandwich was observed through synchrotron radiation. Meanwhile, the effect of the FSW in foaming is explored. The FSW leads to the early formation of cracks in the core layer of powder in the weld zone. The heterogeneous nucleation of bubbles occurs at the interface and forms small pores. The evolutionary processes of small pores promote interfacial fusion. In addition, the presence of the panel changes the state of the melt at the interface, which benefits the fusion of the melt at the interface.